2016
DOI: 10.1186/s12906-016-1168-z
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced liver injury associated with Complementary and Alternative Medicine: a review of adverse event reports in an Asian community from 2009 to 2014

Abstract: BackgroundThe use of Complementary and Alternative Medicine (CAM) has been increasing over the years. A recent review of adverse event reports (AERs) associated with CAM in Singapore found a notable number of AERs submitted. The objectives of this study are to analyse hepatotoxicity cases associated with CAM in Singapore based on spontaneous adverse event reporting to the Health Sciences Authority (HSA), and to highlight safety signals for specific herbal ingredients.MethodsAERs associated with CAM and hepatot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
44
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 57 publications
2
44
1
2
Order By: Relevance
“…LEVERCOL ® and Jacko ® are health supplements [11, 13]. They also report that 60% and 5% of patients developed an acute hepatitis type or cholestatic hepatitis type, respectively [14], corresponding with the present report that LEVERCOL ® and Jacko ® induced acute hepatitis. In the United States, out of 647 adults with liver disease, 41% reported using complementary and alternative medicine, compared with 33% in adults without liver disease [15].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…LEVERCOL ® and Jacko ® are health supplements [11, 13]. They also report that 60% and 5% of patients developed an acute hepatitis type or cholestatic hepatitis type, respectively [14], corresponding with the present report that LEVERCOL ® and Jacko ® induced acute hepatitis. In the United States, out of 647 adults with liver disease, 41% reported using complementary and alternative medicine, compared with 33% in adults without liver disease [15].…”
Section: Discussionsupporting
confidence: 80%
“…In Asian communities, the majority (74%) of patients with hepatotoxicity associated with the use of complementary and alternative medicine were above 40 years of age and 49% were male [14], although the present case was a 24-year-old man. Teo et al [14] also reported that traditional Chinese medicine, health supplements, and other traditional medicines, including Malay Jam and Indian Ayurveda products, caused liver injury in 62, 28, and 11%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bupleuri radix and Scutellariae radix are the most frequently implicated herbs in a large‐population prospective study (Melchart et al, ) and in several cases of acute liver injury as within a particular formula “Sosiho‐Tang” (Itoh, Marutani, Nishijima, Matsuo, & Itabashi, ). Scutellariae radix is one of the most common hepatotoxic herbs in other studies (Teo et al, ; Woo et al, ). A skullcap diterpenoid, a major component of Scutellariae radix , induces apoptosis of hepatocytes through transformation into reactive metabolites by cytochrome P‐450 3A (Haouzi et al, ).…”
Section: Discussionmentioning
confidence: 96%
“…It has a wide range of functions including, detoxifications, protein synthesis, and production of biochemicalʾs necessary for digestion. Liver disease has become one of the major causes of morbidity and mortality in human all over the world and hepatotoxicity due to drugs appears to be the most common contributing factor in this regard [32].N-Acetyl-p-Aminophenol (APAP), also known as acetaminophen, is the most commonly used over-the-counter antipyretic and analgesic drug. APAPinduced toxicity is considered as one of the primary causes of acute liver failure; numerous scientific reports have focused majorly on APAP hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%